Combining isotopic tracers (222Rn and δ13C) for improved modelling of groundwater discharge to small rivers. Issue 12 (21st December 2014) - Lefebvre, K.; Barbecot, F.; Larocque, M.; Gillon, M.
Abstract In regions where aquifers sustain rivers, the location and quantification of groundwater discharge to surface water are important to prevent pollution hazards, to quantify and predict low flows and to manage water supplies. 222Rn is commonly used to determine groundwater discharge to rivers. However, using this isotopic tracer is challenging because of the high diffusion capacity of 222Rn in open water. This study illustrates how a combination of isotopic tracers can contribute to an enhanced understanding of groundwater discharge patterns in small rivers. The aim of this paper is to combine 222Rn and δ13CDIC to better constrain the physical parameters related to the degassing process of these tracers in rivers. The Hallue River (northern France) was targeted for this study because it is sustained almost exclusively by a fractured chalk aquifer. The isotopes 222Rn, δ13CDIC, δ2H and δ18O were analysed along with other natural geochemical tracers. A mass balance model was used to simulate 222Rn and δ13CDIC. The results of δ2H and δ18O analyses prove that evaporation did not occur in the river. The calibration of a numerical model to reproduce 222Rn and δ13CDIC provides a best‐fit diffusive layer thickness of 3.21 × 10−5 m. This approach is particularly useful for small rivers flowing over carbonate aquifers with high groundwater DIC where the evolution of river DIC reflects the competing processes of groundwater inflow and CO2 degassing. This approach provides a means to evaluate groundwater discharge in small ungauged rivers. Copyright © 2014 John Wiley & Sons, Ltd.